Analysis of maize photosyntheis parameters and whole plant oxidative damage under long-term drought. - LAVINSKY, A. O. (2015)
We test if maize maintain yield under long-term drought throught improvement of photosyntheis (A) coupled with up-regulation of the antioxidant system induced by increase in levels of abscisic acid (ABA). Four maize genotypes with constrasting drought tolerance: BRS1010 and 2B710 (sensitive) and DKB 390 and BRS1055 (tolerant) in two soil water levels, field capacity (FC) and water deficit (WD) were used. WD was applied at the pre-flowering stage for 12 days, and oxidative damage was measured as malondialdehyde (MDA) accumulation in whole plant. Plants from tolerant genotypes DKB390 and BRS1055 showed higher A and had no signal of oxidative damage compared to sensitive genotypes 2B710 and BRS1010 under WD, resulting in a higher yield attributes. For our surprising, it was dissociated from up-regulation of the antioxidant system ABA-mediated. In turn, plants from two sensitive genotypes under WD showed compared to FC consistent reduction of A due to mesophyll conductance (gm) limitation. Only WD plants from sensitive genotype BRS1010 presented leaf ABA levels increased related to its counterparts under FC; however, due to the inactivation of catalase activity the oxidative damage control was not effective, resulting a hardly MDA acumulation in both leaves and roots. The maize tolerance under long-term drought is linked to scape of gm decline.